Intelligent electrical systems : a step towards smarter Earth : Proceedings of the International Conference on Industrial Electronics Mechatronics Electrical & Mechanical Power (IEMPOWER 2019), November 21-23, 2019, Kolkata, India - Chakrabarti, Satyajit; Panja, Ayan Kumar; Bar, Aun Kr (Conference proceedings series on information and communications technology, 2021)
The conference aims to provide a premier platform for Engineers, researchers, scientists and academicians to present their work in the emerging areas such as Renewable Energy, Energy storage, Power Electronics & drives, Smart devices and communication systems, Artificial Intelligence, Robotics, Networks an IoT, Control and automation etc.